1 |
3 |
1 |
2 |
∴f′(x)=x2-(2a-1)x+a2-a-f′(a),
∴f′(a)=a2-(2a-1)a+a2-a-f′(a),
∴f'(a)=0.
(2)∵f(X)=
1 |
3 |
1 |
2 |
∴f′(x)=x2-(2a-1)x+a2-a-f′(a),
∴f′(a)=a2-(2a-1)a+a2-a-f′(a),
∴f′(a)=0.
∴f′(x)=x2-(2a-1)x+(a2-a)=[x-(a-1)](x-a),
令f′(x)>0,得x<a-1,或x>a;令f′(x)<0,得a-1<x<a,
∴f(x)在(-∞,a-1]上單調(diào)遞增,在[a-1,a]上單調(diào)遞減,在[a,+∞)上單調(diào)遞增,
∵0≤a≤1,∴f(x)在x∈[0,1]上的最小值為f(a)=
1 |
3 |
1 |
2 |
∴
1 |
3 |
1 |
2 |
即b>-
1 |
3 |
1 |
2 |
令g(x)=?
1 |
3 |
1 |
2 |
則g′(x)=-x2+x=-x(x-1)≥0,
∴g(x)在x∈[0,1]上單調(diào)遞增,
∴1≤g(x)≤
7 |
6 |
∴b>
7 |
6 |